Impact of Spodoptera frugiperda (Lepidoptera: Noctuidae), on maize yield in humid tropical zones of Central Africa - Agbodzavu, K.M.; Nanga, S.N.; Abang, A.F.; Fotso-Kuate, A.; Bamba, Z.; Masso, C.; Fiaboe, K.K.M. (Oxford University Press, 2024)
Fall armyworm, Spodoptera frugiperda Smith, became the most important maize pest in Africa in 2016, with management based on chemical pesticides. High yield losses across the continent were predicted based on farmers’ perceptions, but existing agroecological differences were not considered. In the Democratic Republic of Congo, experiments were conducted to assess fall armyworm damage and yield losses in maize farms with and without treatment. The study included 2 seasons in the Kipopo wetland in 2020 and 2021, one rainy season in Kanyameshi in 2021, 2 rainy seasons in Mulungu in 2020 and 2021, and one season in a wetland on the Bishibiru site in 2020. In addition, the research was also conducted at 4 sites in Cameroon from September to December 2020 and from March to July 2021. High levels of damage incidences were recorded, but the density of larvae per plant was low, with low to moderate levels of damage severities in different seasons and sites. Treatment significantly reduced the number of fall armyworm larvae and their damage severity. However, the high infestation levels did not significantly reduce yield. Cost–benefit ratios were either negative or, in most cases, less than 1. In the best case, the use of pesticides only allowed the recovery of the amount used for the intervention. We discussed the implications of these findings for fall armyworm management in humid tropical agroecology.